PERFORMANCE EVALUATION OF NATURAL COAGULANTS FOR WASTEWATER TREATMENT - Muhammad Imran; Shahbaz Nasir Khan; Saba Abid; Hafiz Muhammad Safdar Khan (Science Heritage Journal)
Fewer water resources and Wastewater is the main problem these days. There are many methods to treat water, one of them is coagulation and flocculation, used to remove impurities, turbidity, and absorbed metals in water. Aluminum, iron coagulant, charcoal, alum, and many other chemical methods are used for this purpose in industries. But these coagulants have bad effects on human health. So this study is to focus on alternatives of these coagulants by finding efficient natural coagulants. Good natural coagulants are those that contain protein soluble properties and basicity. Some of the Alternative coagulants are chosen; Moringa seed, neem leaves, eggshells, orange peels, and banana peels. Different coagulants are used to reduce TDS and other dissolved impurities from an industrial outlet water sample, to check the characteristics and efficiency of natural coagulants. These natural coagulants were then compared with commercially used coagulants. Each coagulant was studied in the spectrometer at a different wavelength and dilution, the sample was tested at different times after 5,10,15,20 minutes and by changing coagulant concentration. Moringa seed is most efficient, it shows up to 97% turbidity removal and 73% TDS removal. The controlled amount of banana peel absorbs up to 97% methyl orange dye. These Natural coagulants are easily available, cheap rates and have no side effects. Natural coagulants are a good alternative to commercially available natural coagulants. These can be prepared locally to treat sewage water and rainwater before discharge into groundwater or for use in agriculture purpose.